The Role of Study on Green Marketing Practices as a Moderation Variable in the Relationship of Service Quality and Store Atmosphere to Purchase Decisions in Management Students: A Structural Equation Modelling Study - Fadillah, Fadillah; Husen, Achmad; Suparno, Suparno; Martono, Adi (PT FORMOSA CENDEKIA GLOBAL, 2025)
Green marketing focuses on sustainability and environmental protection to meet consumer concerns about the environment. This study examines the relationship between Green Marketing Practices, Service Quality, Store Atmosphere, and Purchase Decisions among 384 management students using SEM-PLS analysis. Results show that Service Quality and Store Atmosphere significantly influence Purchase Decisions, but Green Marketing Practices do not act as a moderating variable. Practical elements like Service Quality and Store Atmosphere play a more critical role in driving Purchase Decisions than academic understanding of Green Marketing Practices. Store managers should prioritize these practical factors to enhance purchase outcomes.